IMPLEMENTASI MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE) DALAM MENINGKATKAN KEMAMPUAN KOGNITIF SISWA DI SEKOLAH DASAR - Rahmah, Ulfatu; Jalal, Muhaiminah; Aryastuti Hasanah, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science learning in IPAS subjects in elementary schools still faces problems in the form of low student engagement and limited use of interactive learning media, resulting in suboptimal understanding of science concepts. The application of the RADEC learning model has not been studied in depth in terms of the experiences and perceptions of teachers and students. This study aims to gain an in-depth understanding of the meaning, experiences, and perceptions of teachers and students regarding the use of the RADEC learning model in IPAS learning in elementary schools. This study uses a qualitative approach with a case study design. The research subjects include classroom teachers and fourth-grade students at SDN 131/IV Kota Jambi. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis was conducted thematically through data reduction, data presentation, and conclusion drawing. The results showed that students perceived the RADEC learning model as fun and motivating, while teachers considered RADEC effective in increasing student engagement and facilitating active learning. This study concluded that the application of the RADEC learning model provided a meaningful learning experience and was in line with the characteristics of students in the digital age.